Patterns of Acquisition and Differential Retention of Helping Skills and their Effect on Client Verbal Behaviour - Gluckstern, Norma; Ivey, Allen; Forsyth, Douglas (Canadian Journal of Counselling and Psychotherapy, 2012)
Fourteen community people were trained as drug counsellors through 40 hours of training in microcounselling. The impact of this training on acquisition of counselling skills and their effect on client behaviour was investigated. It was concluded that peer counsellors were successful in modifying the verbal behaviour ofclients in desired directions. The data also reveal some counsellor leads and microcounselling skills lose strength and may, over time disappear while others are maintained. Implications of the decay/maintenance phenomena as they relate to counsellor effectiveness need further investigation.